GE_GERICHTE A/786/2010 vom 28. Juni 2010 - GE Cour de justice (2010)
; PC ; CONDITION D'ASSURANCE ; RESSORTISSANT ÉTRANGER ; INVALIDITÉ(INFIRMITÉ) ; PROCÉDURE ; QUESTION PRÉJUDICIELLE | RAI 41 al.1 let k; LPC 5 al. 3